# 92 collocation for first order systems let us extend

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: k j =1 = j6 y ( )L ( ) + R( ) ik =1 k ; = ( ; 1 )( ; 2) : : : ( ; ; ( ; 1)( ; 2 ) : : : ( ; j k k j k R=y k 0 i 1 i k 2 ::: iJ Y J j x=x 1+ h i; i ik (9.2.3a) 0 1 )( 1 )( k; k; ; +1) : : : ( ; ) ; +1) : : : ( ; ) k k J k k 0 k (9.2.3b) (; ) (9.2.3c) 1 =1 (9.2.3d) j =x 1+ h: i; J (9.2.3e) i The image of the collocation points , k = 1 2 : : : J , are ordered such that k 0 1 < 2< 14 < J 1: (9.2.3f) The divided di erence y 1 2: : : : ] will be de ned shortly. Substituting (9.2.3a) into (9.2.2) yields 0 i i iJ X J y(x) = y(x 1) + h i; i y( ) ik =1 k Z 0 X J y( ) = y(x 1 ) + h ij i; i k =1 y( ) ik a= Z jk and j 0 J i =1 i i i; i k =1 y( ) b= k and E= ik Z1 0 R( )d : 0 (9.2.5c) 0 ik jk i L ( )d + h k i j Z1 0 R( )d : (9.2.6a) R( )d : (9.2.6b) k Z1 0 y(x ) = y(x 1) + h i; j L ( )d 0 we have i i y ( )a + h E : Z1 0 Letting k (9.2.5b) Evaluating (9.2.4) at x = x yields y(x ) = y(x 1) + h L ( )d + h (9.2.4) R( )d : k J Z R( )d : (9.2.5a) X y( ) = y(x 1) + h X 0 k j i; i L ( )d 0 Then ij j...
View Full Document

## This document was uploaded on 03/16/2014 for the course CSCI 6820 at Rensselaer Polytechnic Institute.

Ask a homework question - tutors are online